Genetic Interactions among Regulators of Septin Organization - Gladfelter, Amy S. (American Society for Microbiology, 2004)
Septins form a cortical scaffold at the yeast mother-bud neck that restricts the diffusion of cortical proteins between the mother and bud and serves as a signaling center that is important for governing various cell functions. After cell cycle commitment in late G(1), septins are assembled into a narrow ring at the future bud site, which spreads to form a mature septin hourglass immediately after bud emergence. Although several septin regulators have been identified, it is unclear how they cooperate to assemble the septin scaffold. We have examined septin localization in isogenic strains containing single or multiple mutations in eight septin organization genes (CDC42, RGA1, RGA2, BEM3, CLA4, GIN4, NAP1, and ELM1). Our results suggest that these regulators act largely in parallel to promote either the initial assembly of the septin ring (CDC42, RGA1, RGA2, BEM3, and CLA4) or the conversion of the ring to a stable hourglass structure at the neck (GIN4, NAP1, and ELM1). Aberrant septin localization patterns in mutant strains could be divided into apparently discrete categories, but individual strains displayed heterogeneous defects, and there was no clear-cut correspondence between the specific mutations and specific categories of defect. These findings suggest that when they are deprived of their normal regulators, septin scaffolds collapse into a limited repertoire of aberrant states in which the nature of the mutant regulators influences the probability of a given aberrant state.